5-Bromo-3-cyclohexylsulfonyl-2,7-dimethyl-1-benzofuran - Choi, Hong Dae (International Union of Crystallography, 2011)
In the title compound, C(16)H(19)BrO(3)S, the cyclohexyl ring adopts a chair conformation. In the crystal, molecules are linked through weak C—H⋯O hydrogen bonds and Br⋯O contacts [3.211 (1) Å].